Desquamative Gingivitis as the Sole Manifestation in Oral Lichen Planus: Report of Case and Brief Literature Review - Shazina Saeed1 , Shamimul Hasan2 , Rajat Panigrahi3 , Sourav Panda4 , SK. Tarique Ajiz5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Mouth is the mirror of the human body that reflects systemic disorders, and various systemic pathologiesfind expression in the oral region. Oral manifestations may be the initial feature or the only presenting signin mucocutaneous diseases. Mucocutaneous disorders share two features in common: An immune-mediatedpathogenesis and possibly common clinical appearance termed as ‘Desquamative gingivitis’. Desquamativegingivitis is mostly a manifestation of a wide array of vesiculobullous disorders; however, it may also resultdue to endocrine disturbances, chronic infections, and allergic/chemical reactions. Hereby, presenting a caseof oral lichen planus with Desquamative gingivitis as the sole manifestation in a 35-year-old female patient.